Spatial, temporal, and species variation in prevalence of influenza A viruses in wild migratory birds. - Vincent J Munster; Chantal Baas; Pascal Lexmond; Jonas Waldenström; Anders Wallensten; Thord Fransson; Guus F Rimmelzwaan; Walter E P Beyer; Martin Schutten; Björn Olsen; Albert D M E Osterhaus; Ron A M Fouchier (PLoS Pathogens, 2007)
Although extensive data exist on avian influenza in wild birds in North America, limited information is available from elsewhere, including Europe. Here, molecular diagnostic tools were employed for high-throughput surveillance of migratory birds, as an alternative to classical labor-intensive methods of virus isolation in eggs. This study included 36,809 samples from 323 bird species belonging to 18 orders, of which only 25 species of three orders were positive for influenza A virus. Information on species, locations, and timing is provided for all samples tested. Seven previously unknown host species for avian influenza virus were identified: barnacle goose, bean goose, brent goose, pink-footed goose, bewick's swan, common gull, and guillemot. Dabbling ducks were more frequently infected than other ducks and Anseriformes; this distinction was probably related to bird behavior rather than population sizes. Waders did not appear to play a role in the epidemiology of avian influenza in Europe, in contrast to the Americas. The high virus prevalence in ducks in Europe in spring as compared with North America could explain the differences in virus-host ecology between these continents. Most influenza A virus subtypes were detected in ducks, but H13 and H16 subtypes were detected primarily in gulls. Viruses of subtype H6 were more promiscuous in host range than other subtypes. Temporal and spatial variation in influenza virus prevalence in wild birds was observed, with influenza A virus prevalence varying by sampling location; this is probably related to migration patterns from northeast to southwest and a higher prevalence farther north along the flyways. We discuss the ecology and epidemiology of avian influenza A virus in wild birds in relation to host ecology and compare our results with published studies. These data are useful for designing new surveillance programs and are particularly relevant due to increased interest in avian influenza in wild birds.